Introduction: symposium on Marxist approaches to EU Law - Robert Knox; Eva Nanopoulos; Andrew Woodhouse (European Law Open)
Over the last two decades, Marxism has experienced a significant revival, including in the discipline of law. The 2003 Iraq War and, perhaps more obviously, the 2008 financial crisis posed questions about the relationship between law, capitalism and imperialism that mainstream legal scholarship had difficulty answering. One marked exception to this revival has been in the field of European Union (EU) law. EU law scholarship, perhaps understandably given that few Member States participated in the invasion, had little to say about the Iraq War. For its part, the 2008 financial crisis and its manifestation in Europe as the ‘Euro-Crisis’ prompted a ‘critical turn’ in EU legal studies.1 However, these two movements – the Marxist tradition and critical EU law scholarship – have largely failed to meet. Marxist analyses of EU law, let alone the development of a full-blown Marxist theory of EU law, remain almost non-existent.